2020
DOI: 10.3389/fmech.2019.00069
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Vorticity-Driven Wildfire Behavior Using Near-Field Techniques

Abstract: Dynamic modes of fire propagation present a significant challenge for operational fire spread simulation. Current two-dimensional operational fire simulation platforms are not generally able to account for the complex interactions that drive such behaviors, and while fully coupled fire-atmosphere models are able to account for dynamic effects to an extent, their computational demands are prohibitive in an operational context. In this paper we consider techniques for extending two-dimensional fire spread simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Using the foregoing assumptions, Sharples and Hilton (2019) showed that the pyrogenic vertical vorticity due to a line source of ambient horizontal vorticity s xy can be written as:…”
Section: Near-field Modelling Of Vlsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the foregoing assumptions, Sharples and Hilton (2019) showed that the pyrogenic vertical vorticity due to a line source of ambient horizontal vorticity s xy can be written as:…”
Section: Near-field Modelling Of Vlsmentioning
confidence: 99%
“…where k is a constant based on factors including the vertical speed of the plume, the vortex strength, the nominal mid-flame height and ν (Sharples and Hilton, 2019). The function δ(x) is a Dirac delta function, the variable x is the nearest point on the line source to position x, φ is the distance from the fire perimeter andn is the outward normal of the fire perimeter.…”
Section: Near-field Modelling Of Vlsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coupling between surface fire and wind on larger scales involves interactions between fire-generated convection and frontal motion (e.g., Hilton et al [17]), background and induced local vorticity, and the tilting of the surrounding horizontal vorticity field. Sharples and Hilton [18] isolated and described such an effect in their model of flow over a ridge, with the associated vorticity-induced lateral fire spread. In this mechanism, the vorticity of the background flow is lifted by the fire plume, tilted, and modifies the horizontal flow.…”
Section: Introductionmentioning
confidence: 99%